KELOMPOK WIRA USAHA IBU ‘MANDIRI’ DI DESA PARIA, WAJO – SULAWESI SELATAN - -, Feizarina (Jurnal Ilmiah Ecosystem, 2016)
Paria village is one of the villages of the District Majauleng, Wajo, SouthSulawesi. The majority of the population is farmer and the Civil Service, has a page /home gardens that grow coconut trees. These conditions will certainly provide manyopportunities coconut production of every household in the region. If at any householdstore coconuts falling on their inventory in the warehouse, then made the traditionalcooking oil on the end result will produce blendo. The utilization of this limited blendostill need to be handled to be made into confectionary are more varied andeconomically better than any housewife group in this region.Standard manufacture of one kilogram of cooking oil traditional / kelntik and 500grams blendo produced from coconuts seven medium-size (1: 7). For the re sep makeschips "Black Coconut" requires 250 grams blendo. From this recipe produces 25 minbottled fruit size of 250 grams of chips, which is packed with packaging made fromalluminium foil, models highlighter (Packaging can stand steady despite heavy).Predicted with a selling price of Rp. 5000 / fruit, it will generate a gross income of Rp,125,000 per production, the business capital of Rp. 70,000 / production.Making chips are for confectionary chips snacks is one of the well-loved by thegeneral public, has durability / shelf life long enough. Variations confectionary createdin an effort to boost the creativity of the business group housewife "Independent" to takeadvantage of existing production, addition of this business group will create a powerfulnew business field for the surrounding communityIn order to provide more benefits that it is conducted inScience and technology for rural communities in the Paria IbM for business groupshousewife "Independent" in the village of Paria .. In addition, the utilization ofconfectionary packaging technology that meets the security elements, good shelf life, amore attractive appearance, so it will have an impact on sales of the product better.That aspect of production to marketing is an aspect that gets the attention with goodpackaging. Besides creating an entrepreneurial spirit among housewives who have theeffects of increasing economic value in this region.